Desta para a melhor: a presença das viúvas machadianas no Jornal das famílias - Silva, Jaqueline Padovani da [UNESP] (2014)
Machado de Assis's vast contribution throughout the 16 years in which the magazine Jornal das famílias, by Baptiste-Louis Garnier, was issued points out to a literary set, which disposes of about eighty distributed short stories, mostly seriate. Mainly addressed to a female audience reader, such narratives explore themes to please nineteenth century women, thus, having their focus mostly on subjects related to love and marriage. This research emphasizes the nuptial scenario explored by Garnier's printing in order to analyze Machado's work concerning widowhood and the possible freedom assumed by women within the social boundaries imposed by matrimony and by the paternalistic circumstance, characteristic of Brazilian society from the nineteenth century. Having the Jornal das famílias, in its full longevity, as basis for this study, Machado's 21 short stories were examined, all of which contained plots presenting widow characters who were relevant to the dramatic development of the text. Through the analysis of the bereaving female figures, it was possible to nuance the little widow's behavior by way of considering the explored facts in each narrative, Machado's attentive and critical eye, and also the conditions of the production circumscribed to the journal's current ideology. This proposal made use of the notion, presented by Cultural History, that the texts should be understood by means of the evaluation of supporting material. In order to do this research, it was essential the investigations carried on by the Sociology of Literature, by Machado's critical fortune, and also by the History of the nineteenth century Brazilian press. Finally, it is pertinent to add that, despite the conservatism preached by the Jornal, it was observed that Machado's widow figure takes up modulation spaces between the magazine's moralistic amenity and its critical mocking - even though...